Bahan Ajar Berbasis Etnomatematika Makanan Tradisional Cilacap pada Materi Bangun Ruang di Kelas IV SD - Lia Musli'ah; Dindin Abdul Muiz Lidinilillah; Ika Fitri Apriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This research is motivated by the suboptimal use of teaching materials in mathematics learning, especially in spatial geometry material. In addition, educators have never implemented the use of ethnomathematics-based teaching materials in the learning process. Therefore, the purpose of this study is to develop teaching materials in the form of ethnomathematics-based Student Worksheets (LKPD) that highlight traditional Cilacap foods in spatial geometry material for grade IV Elementary School. This study uses the Educational Design Research (EDR) approach model of McKenney and Reeves (2012). The development of this LKPD was designed by considering three important requirements, namely didactic, constructive, and technical requirements. The LKPD design was arranged attractively using the Canva platform which is equipped with appropriate color and image displays. Product trials were conducted on grade IV students of SDN Karangpucung 05 and SDN Tayem Timur 01. The trial results showed that the response of students from SDN Karangpucung 05 was 95% and from SDN Tayem Timur 01 was 97%. Meanwhile, responses from educators showed a percentage of 96% at SDN Karangpucung 05 and 94% at SDN Tayem Timur 01. All responses were in the very appropriate category. Based on the validation results from material experts, as well as student and educator response questionnaires, it can be concluded that this ethnomathematics-based LKPD teaching material is suitable for use in mathematics learning in elementary schools. Keywords: Ethnomatematics, Geometry, Teaching Materials ABSTRAK Penelitian ini dilatarbelakangi oleh kurang optimalnya penggunaan bahan ajar dalam pembelajaran matematika, khususnya pada materi bangun ruang. Selain itu, pendidik belum pernah menerapkan penggunaan bahan ajar berbasis etnomatematika dalam proses pembelajaran. Oleh karena itu, tujuan dari penelitian ini adalah untuk mengembangkan bahan ajar berupa Lembar Kerja Peserta Didik (LKPD) berbasis etnomatematika yang mengangkat makanan tradisional khas Cilacap pada materi bangun ruang untuk kelas IV Sekolah Dasar. Penelitian ini menggunakan pendekatan Educational Design Research (EDR) model McKenney dan Reeves (2012). Pengembangan LKPD ini dirancang dengan memperhatikan tiga syarat penting, yaitu syarat didaktik, konstruktif, dan teknis. Desain LKPD disusun secara menarik dengan menggunakan bantuan platform Canva yang dilengkapi tampilan warna dan gambar yang sesuai. Uji coba produk dilakukan pada peserta didik kelas IV SDN Karangpucung 05 dan SDN Tayem Timur 01. Hasil uji coba menunjukkan bahwa respon peserta didik dari SDN Karangpucung 05 sebesar 95% dan dari SDN Tayem Timur 01 sebesar 97%. Sementara itu, respon dari pendidik menunjukkan persentase sebesar 96% di SDN Karangpucung 05 dan 94% di SDN Tayem Timur 01. Seluruh respon tersebut berada dalam kategori sangat layak. Berdasarkan hasil validasi dari ahli materi, serta angket respon peserta didik dan pendidik, dapat disimpulkan bahwa bahan ajar LKPD berbasis etnomatematika ini layak untuk digunakan dalam pembelajaran matematika di sekolah dasar. Kata Kunci: Etnomatematika, Bangun Ruang, Bahan Ajar